Redistribution in a joint income-wealth perspective: A cross-country comparison - Sarah Kuypers; Francesco Figari; Gerlinde Verbist (University of Essex, Institute for Social and Economic Research (ISER), 2018)
Redistribution is usually understood in terms of income; as a way to rank individuals as well as to determine taxable capacity or benefit eligibility. Yet, it is increasingly argued that more prominence should be given to the joint distribution of income and wealth and interest into the taxation of wealth for redistributive purposes has largely increased. By including the HFCS data into the microsimulation model EUROMOD we add two novel aspects to the literature. First, we include the analysis of taxes on wealth and wealth transfers. Second, we evaluate redistributive effects of tax-benefit systems against the joint income-wealth distribution instead of income only. We show that expressing living standards in terms of both income and wealth results in considerable reranking of individuals, which in turn leads to a lower redistributive impact of tax-benefit systems than is traditionally considered.
Keywords: C15; H24; I3; 330; wealth policies; distributional analysis; EUROMOD; HFCS